2016
DOI: 10.7324/japs.2016.60206
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Properties of Malaysian Tualang Honey and Stingless Bee Propolis against Candida Albicans and Cryptococcus Neoformans

Abstract: Candida albicans and Cryptococcus neoformans can cause life-threatening infections, especially in immunecompromised patients. Treatment with currently available antifungal agents may lead to severe side-effects and emergence of resistant strains. The objective of this study was to evaluate the antifungal properties of MTH and SBP against C. albicans and C. neoformans. Broth dilution method was used to assess the antifungal properties of the MTH and propolis. Different concentrations of the MTH and propolis (0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 44 publications
1
29
0
Order By: Relevance
“…These results showed that the eNEEs could inhibit both of the yeasts tested with narrow ranges of the concentrations but did not exhibit the killing effect of the eNEEs. It is consistent with the antifungal activity of some natural extracts, showing that it could inhibit yeast e.g., C. albicans (Freires et al, 2016;Shehu et al, 2016). Even though the disk diffusion method could not present any effect, the results from broth dilution methods is confidently reported that the eNEEs possessed the antifungal property, especially the anti-yeast effect.…”
Section: The Enees Obviously Demonstrated Both Antibacterial and Antisupporting
confidence: 79%
See 1 more Smart Citation
“…These results showed that the eNEEs could inhibit both of the yeasts tested with narrow ranges of the concentrations but did not exhibit the killing effect of the eNEEs. It is consistent with the antifungal activity of some natural extracts, showing that it could inhibit yeast e.g., C. albicans (Freires et al, 2016;Shehu et al, 2016). Even though the disk diffusion method could not present any effect, the results from broth dilution methods is confidently reported that the eNEEs possessed the antifungal property, especially the anti-yeast effect.…”
Section: The Enees Obviously Demonstrated Both Antibacterial and Antisupporting
confidence: 79%
“…Stingless bees' propolis from different countries has been characterized to have antimicrobial activities against S. aureus, E. coli, C. albicans, Cryptococcus neoformans and several Candida. (Lakshmi et al, 2014;Freires et al, 2016;Shehu et al, 2016). Some propolis and honey affect the proliferation of human cell lines (Pratsinis et al, 2010;Ahmed and Othman, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In another study [42], 5 mg/mL (5000 ppm) of ethanol extract of propolis completely inhibited the radial growth of F. oxysporum on solid media (PDA). Various compounds like phenolics and flavonoids are responsible for their antifungal activity by affecting the permeability of the cytoplasmic membrane, which leads to the total leakage of the cellular constituents such as nucleic acids, proteins and inorganic ions such as phosphate and potassium, leading to complete cell death [43].…”
Section: Microorganismmentioning
confidence: 99%
“…P. aeruginosa and S. pyogenes inoculums prepared by picking up two to three morphologically identical colonies from stock culture which were then suspended in 10 mL of sterile Mueller Hinton broth in sterilized universal bottles. The inoculums were incubated at 37°C for 24 h (Shehu et al 2016).…”
Section: Bacterial Growthmentioning
confidence: 99%